A study of skin marker alignment using different diamond‐shaped light fields for prone breast external‐beam radiation therapy. Issue 11 (27th August 2022) - Xu, Huijun; Cheston, Sally B.; Gopal, Arun; Zhang, Baoshe; Chen, Shifeng; Yu, Suhong; Hall, Andrea; Dudley, Sara
Abstract: For breast cancer patients treated in the prone position with tangential fields, a diamond‐shaped light field (DSLF) can be used to align with corresponding skin markers for image‐guided radiation therapy (IGRT). This study evaluates and compares the benefits of different DSLF setups. Seventy‐one patients who underwent daily tangential kilovoltage (kV) IGRT were categorized retrospectively into four groups: (1) DSLF field size (FS) = 10 × 10 cm 2, gantry angle = 90° (right breast)/270° (left breast), with the same isocenter as treatment tangential beams; (2) same as group 1, except DSLF FS = 4 × 4 cm 2 ; (3) DSLF FS = 4 × 4–6 × 8 cm 2, gantry angle = tangential treatment beam, off‐isocenter so that the DSLF was at the approximate breast center; and (4) No‐DSLF. We compared their total setup time (including any DSLF/marker‐based alignment and IGRT) and relative kV‐based couch shift corrections. For groups 1–3, DSLF‐only dose distributions (excluding kV‐based correction) were simulated by reversely shifting the couch positions from the computed tomography plans, which were assumed equivalent to the delivered dose when both DSLF and IGRT were used. For patient groups 1–4, the average daily setup time was 2.6, 2.5, 5.0, and 8.3 min, respectively. Their mean and standard deviations of daily kV‐based couch shifts were 0.64 ± 0.4, 0.68 ± 0.3, 0.8 ± 0.6, and 1.0 ± 0.6 cm. The average target dose changes after excluding kV‐IGRT for groups 1–3 were−0.2%, −0.1%, and +0.4%, respectively, whereas DSLF‐1 was most efficient in sparing heart and chest wall, DSLF‐2 had lowest lung D max ; and DSLF‐3 maintained the highest target coverage at the cost of highest OAR dose. In general, the use of DSLF greatly reduces patient setup time and may result in smaller IGRT corrections. If IGRT is limited, different DSLF setups yield different target coverage and OAR dose sparing. Our findings will help DSLF setup optimization in the prone breast treatment setting.